Alteration of human hepatic drug transporter activity and expression by cigarette smoke condensate. (1st July 2016) - Sayyed, Katia; Vee, Marc Le; Abdel-Razzak, Ziad; Jouan, Elodie; Stieger, Bruno; Denizot, Claire; Parmentier, Yannick; Fardel, Olivier
Graphical abstract: Abstract: Smoking is well-known to impair pharmacokinetics, through inducing expression of drug metabolizing enzymes. In the present study, we demonstrated that cigarette smoke condensate (CSC) also alters activity and expression of hepatic drug transporters, which are now recognized as major actors of hepatobiliary elimination of drugs. CSC thus directly inhibited activities of sinusoidal transporters such as OATP1B1, OATP1B3, OCT1 and NTCP as well as those of canalicular transporters like P-glycoprotein, MRP2, BCRP and MATE1, in hepatic transporters-overexpressing cells. CSC similarly counteracted constitutive OATP, NTCP and OCT1 activities in human highly-differentiated hepatic HepaRG cells. In parallel, CSC induced expression of BCRP at both mRNA and protein level in HepaRG cells, whereas it concomitantly repressed mRNA expression of various transporters, including OATP1B1, OATP2B1, OAT2, NTCP, OCT1 and BSEP, and enhanced that of MRP4. Such changes in transporter gene expression were found to be highly correlated to those caused by 2, 3, 7, 8-tetrachlorodibenzo- p -dioxin, a reference activator of the aryl hydrocarbon receptor (AhR) pathway, and were counteracted, for some of them, by siRNA-mediated AhR silencing. This suggests that CSC alters hepatic drug transporter levels via activation of the AhR cascade. Importantly, drug transporter expression regulations as well as some transporter activity inhibitions occurred for a range of CSC concentrations similar to those required for inducing drug metabolizing enzymes and may therefore be hypothesized to be relevant for smokers. Taken together, these data established human hepatic transporters as targets of cigarette smoke, which could contribute to known alteration of pharmacokinetics and some liver adverse effects caused by smoking.